Pembinaan Moral di Balai Perlindungan dan Rehabilitasi Sosial Remaja Yogyakarta - Ritonga, Riski Yusuf; Nurjannah (Malewa: Journal of Multidisciplinary Educational Research, 2025)
This study aims to evaluate how effective moral guidance is given to troubled adolescents at the Center for Social Protection and Rehabilitation of Adolescents (BPRSR) Yogyakarta. This study uses a field study method with a qualitative descriptive approach. Informants were selected purposively and consisted of heads of institutions, social workers, psychologists, and counselors who all have direct experience in the process of social rehabilitation of adolescents. Data collection was carried out through observation, in-depth interviews, and documentation. The data analysis technique used the triangulation method and was analyzed using a qualitative descriptive approach. The results of the study showed that the moral guidance program at BPRSR had a positive impact on adolescents in several main aspects, namely: changes in behavior towards a more positive direction, increased self-awareness and discipline, and internalization of moral values ​​such as responsibility, honesty, and empathy. This guidance process is carried out through religious activities, individual and group counseling, skills training, and a holistic psychosocial approach. However, challenges are still found, especially in terms of the lack of support from families which causes some adolescents to experience difficulties when returning to their original environment. Therefore, this study emphasizes the importance of stronger synergy between institutions, families, and communities to ensure the sustainability of the moral rehabilitation process more effectively and sustainably.